Towards optimal 1.5° and 2 °C emission pathways for individual countries: A Finland case study. (October 2019) - Sferra, Fabio; Krapp, Mario; Roming, Niklas; Schaeffer, Michiel; Malik, Aman; Hare, Bill; Brecha, Robert
Abstract: Nationally Determined Contributions (NDCs) submitted so far under the Paris Agreement are not in line with its long-term temperature goal. To bridge this gap, countries are required to provide regular updates and enhancements of their long-term targets and strategies, based on scientific assessments. The goal of this paper is to demonstrate a policy-support approach for evaluating NDCs and guiding enhanced ambition. The approach rests on deriving national targets in line with the Paris Agreement by downscaling regional results of Integrated Assessment Models (IAMs) to the country level. The method of downscaling relies on a reduced complexity IAM: SIAMESE (Simplified Integrated Assessment Model with Energy System Emulator). We apply the approach to an EU28 member state – Finland – with the aim of providing useful insights for policy makers to consider cost-effective mitigation options. Results over the historical period confirm that our approach is valid when national policies are similar to those across the larger IAM region, but must include country-specific circumstances. Strengths and limitations of the approach are discussed. We assess the remaining carbon budget and analyse the different implications of 2 °C and 1.5 °C global warming limits for the emissions pathway and energy mix in Finland over the 21st century. Highlights: We downscale regional IAMs results to the country level with a new model: SIAMESE. Results over the historical period confirm the validity of our approach. Using Finland as an example, we analyse CO2 emissions for both 1.5 °C and 2 °C pathways. We calculate the remaining carbon budget until mid-century and 2100 for the example case of Finland.